Review article: Have emergency department time‐based targets influenced patient care? A systematic review of qualitative literature. (23rd February 2021) - Walker, Katie; Honan, Bridget; Haustead, Daniel; Mountain, David; Gangathimmaiah, Vinay; Forero, Roberto; Mitchell, Rob; Martini, Ella; Tesch, Greg; Bissett, Ian; Jones, Peter
Abstract: Time‐based targets for ED length of stay were introduced in England in 2000, followed by the rest of the UK, Canada, Ireland, New Zealand, and Australia after ED crowding was associated with poor quality of care and increased mortality. This systematic review evaluates qualitative literature to see if ED time‐based targets have influenced patient care quality. We included 13 studies from four countries, incorporating 617 interviews. We conclude that time‐based targets have impacted on the quality of emergency patient care, both positively and negatively. Successful implementation depends on whole hospital resourcing and engagement with targets. Abstract : This is a qualitative review of literature evaluating how time‐based‐targets impacted on patient quality of care in emergency departments. Thirteen studies from four countries, with the views of 617 stakeholders are presented. The impact of time‐based‐targets is varied, can be both positive and negative and successful implementation depends on whole hospital resourcing and engagement with targets.